2009
DOI: 10.1007/s11661-009-9914-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Cryomilled Ni Superalloy by Spark Plasma Sintering

Abstract: The mechanical behavior of ultra-fine-grained (UFG) INCONEL 625 superalloy prepared via cryomilling and spark plasma sintering (SPS) was studied. The workhardening response of the ultra-fine-grained (600 to 700 nm) INCONEL 625 was compared to that of the material with a 1-lm grain size and the results showed normal work hardening for the latter material but not for the former. Moreover, the results suggest that a combination of high strength and good ductility can be simultaneously obtained in the UFG INCONEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Such trend is shown for Tungsten [24], Inconel 625 (Ni-based super alloy) [25], and Al-2024 [26], as examplesshown in Figs. 2 and 3.…”
Section: Sps Temperaturesupporting
confidence: 60%
“…Such trend is shown for Tungsten [24], Inconel 625 (Ni-based super alloy) [25], and Al-2024 [26], as examplesshown in Figs. 2 and 3.…”
Section: Sps Temperaturesupporting
confidence: 60%
“…It is reported that pore formation during powder sintering reduced grain growth due to the pinning effect exerted by the pores. This also happened in the SPS method and has been reported in literature [41,42]. Sample C has the largest grain size and possesses the least density, and this is because the sintered alloy keeps the memory of the starting powder particle size.…”
Section: Microstructure Of the Sintered In738lc Alloyssupporting
confidence: 56%
“…It has several advantages over conventional sintering owing to its higher heating rates and shorter sintering time. [17][18][19] Experimental…”
Section: Introductionmentioning
confidence: 99%